(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
the article reveals that sport helps a child develop harmoniously, strengthens the nervous system, immunity, and has a positive effect on the health of the body as a whole. In addition, playing sports teaches a child discipline, builds character, develops willpower, and the ability to set goals and achieve them. Physical education is necessary for a person at all periods of his life. In childhood and adolescence, they contribute to the harmonious development of the body. In adults, they improve the morphofunctional state, increase performance and maintain health. Any physical exercise improves heart function. Sport brings positive emotions and discipline to a person’s life. Exercising strengthens the body, improves muscle memory and coordination